Implementing Supplemental Fuel System for Testing Sustainable Aviation Fuel on TKT-1 Micro Turbojet Engine - Kazzaz, Mhd Bashar Al; Beneda, Karoly Tamas (SACI (International Symposium on Applied Computational Intelligence and Informatics. Online), 2024)
Sustainable Aviation Fuel (SAF) research has been gaining a lot of focus in the past era, the proof of that increased focus can be found in the various articles and investigations that are in the pipeline dealing with this subject. As this growing attention rises noticeably, so does the scientific effort to find the most suitable mixing ratios between the SAF and standard fossil fuels to keep the efficiency of the turbine engines but at the same time decrease the unwanted emissions. Most of the studies on this topic aim to mix the fuels before filling the fuel tank and operating the entirety of the engine fuel nozzles on this new fuel mixture. However, in this article, a new methodology was introduced by which only one nozzle out of the four will be used to inject the investigated mixture. This article describes a modification for the TKT-1 micro turbojet engine by designing and implementing a supplemental fuel system for the purpose of testing SAF. It aims to improve the assessment and integration of SAF by using separate hardware elements independently of the original components. The study's goal is to create a testing platform for evaluating the performance, effectiveness, and emissions of several types of SAF in a real jet engine operating environment. It adds to the ongoing efforts to develop and implement environmentally friendly aviation solutions, addressing the pressing demand for sustainable alternatives in the aviation sector.